PENGARUH KONDISI KEUANGAN PERUSAHAAN PADA KUALITAS LABA - Merintan Berliana Simbolon; Indriyanti Indriyanti (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study is to obtain empirical evidence of the influence of the company's financial condition on earnings quality. The company's financial condition consists of profit growth, profitability, liquidity, and leverage. In this study, earnings quality was measured using a modified discretionary accrual by Kothari (2005). The samplethis study is a manufacturing company with a sub-sector of food and beverage companies listed on the Indonesia Stock Exchange in 2016-2019. The sampling technique used purposive sampling. From the results of this purposive sampling, 20 samples were obtained with a total of 78 observations. The statistical model used in this study was multiple linear regression analysis, which was then processed using SPSS for Windows ver 21.00. The results in this study indicate that the leverage variable has a negative effect on earnings quality. However, the variables of profit growth, profitability, liquidity have no effect on earnings quality.